Development of a behavioural marker system for scrub practitioners' non‐technical skills (SPLINTS system). Issue 2 (15th April 2012) - Mitchell, Lucy; Flin, Rhona; Yule, Steven; Mitchell, Janet; Coutts, Kathy; Youngson, George
Abstract Rationale, aims and objectives Adverse events still occur despite ongoing efforts to reduce harm to patients. Contributory factors to adverse events are often due to limitations in clinicians' non‐technical skills (e.g. communication, situation awareness), rather than deficiencies in technical competence. We developed a behavioural rating system to provide a structured means for teaching and assessing scrub practitioners' (i.e. nurse, technician, operating department practitioner) non‐technical skills. Method Psychologists facilitated focus groups (n = 4) with experienced scrub practitioners (n = 16; 4 in each group) to develop a preliminary taxonomy. Focus groups reviewed lists of non‐technical‐skill‐related behaviours that were extracted from an interview study. The focus groups labelled skill categories and elements and also provided examples of good and poor behaviours for those skills. An expert panel (n = 2 psychologists; n = 1 expert nurse) then used an iterative process to individually and collaboratively review and refine those data to produce a prototype skills taxonomy. Results A preliminary taxonomy containing eight non‐technical skill categories with 28 underlying elements was produced. The expert panel reduced this to three categories (situation awareness, communication and teamwork, task management), each with three underlying elements. The system was called the Scrub Practitioners' List of Intraoperative Non‐Technical Skills system. A scoring system and a user handbook were also developed. Conclusion A prototype behavioural rating system for scrub practitioners' non‐technical skills was developed, to aid in teaching and providing formative assessment. This important aspect of performance is not currently explicitly addressed in any educational route to qualify as a scrub practitioner.